EP833 The prognostic impact of sphingosine-kinase 1 expression (SphK1) on ovarian cancer. (1st November 2019) - Drosos, Z; Gevensleben, H; Kommoss, S; Karn, T; Holtrich, U; Graeser-Mayer, M; Anglesio, M; El-Balat, A; Rody, A; Hanker, L
Abstract : Introduction/Background: Sphingosine-Kinase 1 (SphK1), encoded by the SPHK1 gene, is a key enzyme of sphingolipid metabolism and overexpressed in a variety of cancer types. In the present study, we investigated the expression of SphK1 and its prognostic impact on ovarian cancers. Methodology: We used two large retrospective tissue micro array (TMA) cohorts (in total n=763) for performing immunohistochemical analysis of SphK1. The results were correlated with clinico-pathological characteristics and survival. Results: We found that SphK1 expression differed between histological ovarian cancer histotypes with most frequent low expression in clear cell carcinoma ( p <0.001). In addition, low SphK1 expression was shown to significantly correlate with optimal tumour resection ( p <0.001). Kaplan-Meier analysis further revealed that low SphK1 levels were associated with improved progression-free survival (PFS; 65, 23 months [95% confidence interval (CI): 49, 95–80, 50] vs. 51, 42 months [95% CI: 27, 02–75, 82], p =0, 052) and overall-survival (OS; 100, 01 months [95% CI: 83, 64–116, 38] vs. 75, 35 months [95% CI: 59, 85–90, 85], p =0, 049). Subsequently, the prognostic value of SphK1 expression together with clinical factors (i.e. FIGO stage, age, and residual tumour burden after surgery) was substantiated in univariate Cox regression analysis (PFS: hazard ratio (HR)=0, 83 [95% CI: 0, 69–1, 00], p =0, 052; OS: HR=0, 82 [95% CI: 0, 68–1, 00], p =0, 05). Conclusion: Our results suggest that SphK1 expression might be a prognostic factor in ovarian cancer. Low SphK1 expression seems to be associated with prolonged survival, optimal tumour debulking and clear cell subtype. To corroborate these findings, however, our results need to be validated in an independent patient cohort. Disclosure: Nothing to disclose.